Hubungan antara Penerimaan Diri dengan Resiliensi pada Remaja Pesantren Al Kautsar Al Akbar Medan - Putri Keumala Hijriyana; Nurvica Sari; Rina Mirza; Achmad Irvan Dwi Putra (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Adolescents living in pesantren environments face various developmental challenges, including adaptation to boarding school life, academic demands, social adjustment, emotional regulation, and the internalization of religious values. In this context, resilience is an essential psychological capacity that enables adolescents to cope with difficulties, adapt positively, and maintain personal functioning under pressure. Self-acceptance is considered an important psychological factor that may strengthen resilience by helping adolescents recognize, evaluate, and accept their personal strengths and limitations. This study aimed to examine the relationship between self-acceptance and resilience among adolescents at Pesantren Al Kautsar Al Akbar Medan. A quantitative correlational design was employed. The participants consisted of 100 adolescents selected using disproportionate stratified random sampling. Data were collected using a Self-Acceptance Scale consisting of 47 items and a Resilience Scale consisting of 25 items. The reliability of the instruments was examined using Cronbach’s alpha, yielding coefficients of 0.934 for the Self-Acceptance Scale and 0.857 for the Resilience Scale. Data were analyzed using Pearson product–moment correlation. The results showed a significant positive relationship between self-acceptance and resilience (r = 0.666, p < 0.05). These findings indicate that adolescents with higher levels of self-acceptance tend to demonstrate stronger resilience. The analysis also revealed that self-acceptance contributed 44.3% to resilience, while the remaining 55.7% was influenced by other factors beyond the scope of this study. This study highlights the importance of strengthening self-acceptance as part of psychological development and guidance programs in pesantren settings to support adolescents’ resilience, emotional adjustment, and adaptive functioning.